2021
DOI: 10.1155/2021/5586041
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome of Epileptic Patients Receiving Antiepileptic Drugs in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Background. The prevalence and incidence rate of epilepsy were found to be higher in low- and middle-income countries. Uncontrolled epilepsy has a high risk of disability, stigma, discrimination, human rights violations, and premature death. The available studies of controlled seizure in Ethiopia have showed inconsistent results which calls for systematic review and meta-analysis. Therefore, this review intended to show the pooled prevalence of controlled seizure among people with epilepsy receiving antiepilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Several studies found it to be widely used in SSA countries. 12 , 16 , 18 , 20 23 On multivariate logistic regression analysis, the odds of an uncontrolled seizure was fourfold higher in patients with more than five pretreatment seizure episodes as compared with those who had five or less (AOR = 3.98, 95% CI: 1.81–8.75, p = 0.001). Hospital-based studies in Italy, Scotland, India, and Ethiopia showed that frequent seizures before treatment were related to poor seizure control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies found it to be widely used in SSA countries. 12 , 16 , 18 , 20 23 On multivariate logistic regression analysis, the odds of an uncontrolled seizure was fourfold higher in patients with more than five pretreatment seizure episodes as compared with those who had five or less (AOR = 3.98, 95% CI: 1.81–8.75, p = 0.001). Hospital-based studies in Italy, Scotland, India, and Ethiopia showed that frequent seizures before treatment were related to poor seizure control.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using a single population proportion formula with the assumption of 95% confidence level, 5% margin of error, and taking 30% for seizure control in recent study in Ethiopia. 20 A convenience sampling method was used to recruit 320 study subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that almost 80% of epilepsy cases are found in low—and middle-income countries (LMICs) [ 4 ] due to lack of sufficient antiepileptic drugs (AEDs), high cost if any AEDs available, and undesirable outcomes of the existing AEDs [ 8 ]. In the case of Ethiopia, epilepsy is one of the 20 leading causes of mortality, and 5.2 out of 1000 people are prone to ES in their lifetime [ 9 , 10 ]. In general, epilepsy has substantial economic implications, predominantly in Africa, as it triggered a great burden on the underprivileged healthcare system of poor nations [ 11 ] as well as on patients owing to the epilepsy-bound poor QOL, stigma, and discrimination in patients and relatives [ 12 ] that could ominously increase healthcare expenditure and diminish overall productivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, there was discrepancy on the prevalence of controlled seizure among patients receiving antiepileptic drugs that ranges from 8-93.8% [19]. Most patients rely on traditional treatments of epilepsy such as local herbs, holy water, and amulets [20]. Even though there are a number of studies on AED nonadherence, but there is no study about the underlying causes for each low and medium medication adherence.…”
mentioning
confidence: 99%